ANALISIS INTERVAL PERAWATAN KOMPONEN KRITIS UNIT MESIN STITCHING UNTUK MEMINIMUMKAN BIAYA PERAWATAN DAN MENINGKATKAN PRODUKTIVITAS - Fina Andika Frida Astuti; Sugiono Sugiono; Moch. Agus Choiron (Universitas Lambung Mangkurat, 2016)
PT. XYZ is a company producing Exercise Book. To date the company has not been able to meet the high market demand. Historical data shows unit 2015 Stitching machine that serves to menstaples book into one unit has a frequency of engine damage as much as 42 times. The amount of damage to the unit frequency Stitching machines because companies do not yet have a scheduled maintenance activity for each component so that the machine crashes arrived - arrived when operating. To overcome these problems required maintenance interval planning for critical components of the engine unit Stitching. From the analysis of the critical components discovered two critical components of the most influential, namely components Stitching Head and Stang. From the calculation Time to Failure (TTF) and Time to Repair (TTR) of critical components used for distribution menentuan damage and parameter values to calculate the value of MTTF and MTTR. Interval treatment for critical components Stitching Head is 23 days, while for critical components Stang is 72 days. The calculation of the cost of care of two critical components can save costs amounting to 1.310,08 from the previous year and an increase of productivity of 6,77 tonnes